PENGARUH EKSTRAK ETANOL PEGAGAN (Centella asiatica sp.) TERHADAP PEMBENTUKAN MEMORI PASCASTRES LISTRIK KRONIS Kajian Pengaruh Variasi Dosis pada Tikus Putih (Sprague Dawley)terhadap Jarak Tempuh Escape Latency Uji Morris Water Maze - , DEA AMELIA YOLANDA, dr.Dwi Cahyani Ratna Sari, M.Kes., PA (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Centella asiatica sp. (pegagan) has neurotropic and neuroprotective properties which inhibit deterioration of memory because of chronic electrical stress. Studies about effective dose of Centtela asiatica still continued. Objective: To discover the influence of pegagan extractâs dose variation intake towards memory after chronic stress. Method: This study uses that true experimental design with pretest-posttest control design. Subjects are 15 male Sprague Dawley rats. The rats were divided into three groups. Every groups are treated with chronic electrical stress for 4 weeks and aquades (KN), 300mg/kgBW/day of Centella asiatica (KN1) or 600 mg/kgBW/day of Centella asiatica (KP2). The latency distance measure from Morris water maze was used to measure ratsâ memory. Kolmogorov-Smirnov is used to observe the normality of distribution, ANOVA test to compare the measure between different groups and paired t-test to compare pretest and posttest effects. Result: The average of latency distance before chronic electrical stress are 5,71Â±0,77m (KN)